Assessing hydric soils in a gallery forest in the Brazilian Cerrado. (24th January 2013) - Skorupa, A. L. A.; Fay, M.; Zinn, Y. L.; Scheuber, M.
Abstract Hydric soils have important ecological functions such as biodiversity hotspots, hydrological buffering and C storage, but their spatial variability leads to mapping uncertainties. In the Brazilian Cerrado, gallery forests along first‐order streams are used to indicate the occurrence of hydric soils, but this relationship has seldom been tested. This project was designed to determine the occurrence of hydric soils and associated soil organic carbon (SOC) storage in a gallery forest in the Cerrado. Thus, a 19‐km‐long gallery forest was divided into nine transects perpendicular to the stream along which soils were sampled every 10 m with a 1‐m‐depth core sampler. From the 134 cores thus obtained, Munsell colours and redoximorphic features were assessed for each horizon, and the data were used to select the five main soil types for description and characterization. Three soils were well drained (Kandiustox, Plinthic Haplustox and Fluventic Dystrustept), and two were hydric (Plinthaquox and Endoaquent). Hydric soils comprised only 20–30% of the area based on the average transect area where floodplains, mottles, nodules and Munsell values <2 occurred, as well as on calculated hydromorphy indexes. Soil organic carbon stocks to 1 m depth ranged from ca. 120 Mg/ha in well‐drained Oxisols to 860 Mg/ha in the Endoaquent, with overall means between 200 and 400 Mg/ha. Large soil variability is a challenge to mapping hydric soils, which though of limited extent are highly susceptible to degradation following drainage and cultivation.